Uveal Melanoma: Identifying Immunological and Chemotherapeutic Targets to Treat Metastases. Issue 2 (March 2017) - Jager, Martine J.; Dogrusöz, Mehmet; Woodman, Scott E.
Abstract : Abstract: : Uveal melanoma is an intraocular malignancy that, depending on its size and genetic make‐up, may lead to metastases in up to 50% of cases. Currently, no therapy has been proven to improve survival. However, new therapies exploiting immune responses against metastases are being developed. The primary tumor is well characterized: tumors at high risk of developing metastases often contain macrophages and lymphocytes. However, these lymphocytes are often regulatory T cells that may suppress immune response. Currently, immune checkpoint inhibitors have shown marked efficacy in multiple cancers (eg, cutaneous melanoma) but do not yet improve survival in uveal melanoma patients. More knowledge needs to be acquired regarding the function of T cells in uveal melanoma. Other therapeutic options are related to the biochemical pathways. Targeting the RAF‐MEK‐ERK pathway with small molecule MEK inhibitors abrogates the growth of UM cells harboring GNAQ/GNA11 Q209 mutations, suggesting that these aberrant G‐protein oncogenes mediate, at least in part, their effect through this hallmark proliferation pathway. Other pathways are also implicated, such as those involving c‐Jun and YAP. Further studies may show how interference in the different pathways may affect survival.